2006
DOI: 10.1186/1471-2261-6-47
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac involvement in Beagle-based canine X-linked muscular dystrophy in Japan (CXMDJ): electrocardiographic, echocardiographic, and morphologic studies

Abstract: Background: Cardiac mortality in Duchenne muscular dystrophy (DMD) has recently become important, because risk of respiratory failure has been reduced due to widespread use of the respirator. The cardiac involvement is characterized by distinctive electrocardiographic abnormalities or dilated cardiomyopathy, but the pathogenesis has remained obscure. In research on DMD, Golden retriever-based muscular dystrophy (GRMD) has attracted much attention as an animal model because it resembles DMD, but GRMD is very di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 36 publications
4
67
2
4
Order By: Relevance
“…12 Beagle-based dystrophic dogs show mild phenotypes not only in skeletal muscle 13 but also in cardiac muscle. 14 Moreover, we found that the distinctive deep Q waves precede the LV posterobasal lesion on echocardiography and histopathology in CXMD J . 14 The histopathological changes in the conduction system have not been investigated fully, especially in the early stages of the disease, although the expressions of dystrophin and DAPs have been examined in normal systems.…”
Section: Clinical Perspective P 2448mentioning
confidence: 87%
See 2 more Smart Citations
“…12 Beagle-based dystrophic dogs show mild phenotypes not only in skeletal muscle 13 but also in cardiac muscle. 14 Moreover, we found that the distinctive deep Q waves precede the LV posterobasal lesion on echocardiography and histopathology in CXMD J . 14 The histopathological changes in the conduction system have not been investigated fully, especially in the early stages of the disease, although the expressions of dystrophin and DAPs have been examined in normal systems.…”
Section: Clinical Perspective P 2448mentioning
confidence: 87%
“…14 Moreover, we found that the distinctive deep Q waves precede the LV posterobasal lesion on echocardiography and histopathology in CXMD J . 14 The histopathological changes in the conduction system have not been investigated fully, especially in the early stages of the disease, although the expressions of dystrophin and DAPs have been examined in normal systems. [15][16][17][18] The molecular mechanisms of the dystrophin-deficient heart are still unclear.…”
Section: Clinical Perspective P 2448mentioning
confidence: 87%
See 1 more Smart Citation
“…CXMD dog models show longer life span due to slower progression of muscle wasting compared to GRMD dogs (Willmann et al, 2009). Progress of cardiomyopathy in the CXMD dog is also milder than in GRMD (Yugeta et al, 2006).…”
Section: Canine Muscular Dystrophy Modelmentioning
confidence: 93%
“…Sinais clínicos de insuficiência cardíaca congestiva só são verificados em período próximo à morte (Moise et al 1991, Chetboul et al 2004, Pellegrino et al 2007. O eletrocardiograma (ECG) pode apresentar-se distintamente anormal em pacientes com distrofia muscular de Duchenne (Moise et al 1991, Pacioretty et al 1994, Yugeta et al 2006.…”
Section: Introductionunclassified